Matemática financeira aplicada aos ensinos fundamental e médio - Faria, Walquiria Lemes da Silveira (2015)
This study aims to present the importance of the Teaching and Learning of Financial Mathematics from the elementary school to high school. Deals with the mathematical concepts from objectives proposed by PCNs and shows the main formulas related to Financial Mathematics, pointing practical situations for its use. Provides guidelines and proposals so that teachers can work not only with the calculations written manually, but also with the use of technological resources, such as the calculator and the spreadsheets.